Assessing Physical Function and Mobility following Pediatric Traumatic Brain Injury with the NIH Toolbox Motor Battery: A Feasibility Study. (2nd January 2021) - Evans, Emily A.; Cook, Nathan E.; Iverson, Grant L.; Townsend, Elise L.; Duhaime, Ann-Christine; ,
Abstract: Aims: Traumatic brain injury (TBI) can impair physical function in children. The NIH Toolbox Motor Battery (NIHTB-M) was designed to be a brief assessment of physical function, but no studies have examined its use in children with TBI. This study aims to describe the feasibility of using the NIHTB-M to assess children with TBI. Methods: The NIHTB-M was administered to children with TBI 2 weeks (n = 22) and/or 6 months (n = 23) following injury. This descriptive study summarizes participant performance, administration challenges, and the association between NIHTB-M scores, participant characteristics, and subjective report of physical function. Results: Of the NIHTB-M domains, deficits in endurance and balance were most prevalent. Children aged 5 to 16 years could complete the assessment per administration guidelines, except for a few cases (n = 3) where orthopedic injuries limited participation. Younger children (aged 3 to 4) had difficulty following the NIHTB-M directions. Technological issues impacted balance assessment in several cases (n = 6). Conclusion: The NIHTB-M is brief to administer, generally well tolerated by school-aged children and, despite occasional technological challenges, is a feasible performance-based battery for assessment of children with TBI for clinical and research purposes. Additional investigation of psychometric properties and ceiling and floor effects is needed.